Influences on Lung Cancer Screening Initiation and Retention in Rural Alabama - Amy Copeland; Kathy Levy; Claudia M. Hardy; Jennifer C. King; Maureen Rigney (SAGE Publishing, 2023)
Introduction/Objectives: Despite the introduction of lung cancer screening using low dose computed tomography (LDCT), overall screening rates in the U.S. remain low, with certain populations including Black and rural communities experiencing additional disparities. The primary objective of this study was to understand the facilitators of lung cancer screening initiation and retention in Alabama reported by people at risk from mostly rural, mostly Black populations in Jefferson County-including the urban center of Birmingham-and 6 rural counties: Choctaw, Dallas, Greene, Hale, Marengo, and Sumter. Methods: We conducted semi-structured telephone interviews with 58 people who underwent lung cancer screening between December 2019 and January 2022. Participant responses were recorded by the interviewer for analysis. Open-ended responses were coded to identify emergent themes. Results: The most reported influences to initiate screening were information or suggestion from a Community Health Advisor (CHAs) or the supervising county coordinator, suggestion from a friend, or consideration of a personal history of smoking. Most participants reported multiple influences. Physicians were not very influential in decisions to initiate screening, but they were extremely influential in participants' intent to continue screening, both positively and negatively. Knowing the recommended timeline for their annual scans was also a predictor of intention to continue screening. Participants screened during the COVID-19 state of emergency expressed less certainty about dates of next scans and more ambivalence about intention to continue screening. Conclusions: This study shows the benefit of using multiple methods to support increased awareness of and interest in lung cancer screening, particularly when educational messaging through CHAs is used. Clear guideline-based messages from healthcare providers about recommended screening is important for increasing retention. COVID-19 related implementation challenges impacted screening recruitment and retention. Future research is warranted to further explore use of CHAs in lung cancer screening.